Physical Activity Within Rural Families of Overweight Preschool Children: A Pilot - Nuananong Seal; Eleanor Yurkovich (Rural Nurse Organization; Binghamton University, 2009)
The purpose of this descriptive qualitative research was to explore physical activity patterns of families of overweight preschool children aged 3 to 5 years living in a predominantly rural agricultural state. This paper presents the second part of a dually focused study related to healthy eating and physical activity (PA) in this selected population. Methodology used was a focus group discussion with 10 parents of overweight preschool children aged 3 to 5 years. Transcripts were coded and analyzed for emergent themes using N ViVo qualitative analysis software. The findings revealed that all parents were not engaging in any healthy structured PA beyond their daily functioning actions and were not involved in organized sports; however, they had some knowledge of the significance of PA and its benefits for themselves and their children. Also, the parental participants‟ perceptions that the children were active (busy with their own play) and their weights were acceptable (as compared to other children) probably influenced their lack of recognition for the necessity of healthy structured PA. They did identify personal and environmental barriers to engaging in PA. The results provide significant implications for health professionals in planning/developing educational materials for PA interventions, enhancing motivation for PA of rural populations and working towards the reduction of barriers through policy and relevant resource acquisition. Continued research with this population could inform health care providers about more culturally appropriate ways to increase motivation to do and effective environments for physical activity within a rural population.